Evaluating nutrition-sensitive programs: Challenges, methods, and opportunities - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T. (International Food Policy Research Institute, 2016)
The current global evidence base regarding the nutritional impacts of nutrition-sensitive programs, including popular ones such as social safety nets and agriculture development programs, is generally limited due to poor targeting, design, and implementation of programs and, equally important, to suboptimal evaluation designs (Webb-Girard et al. 2012; Ruel and Alderman 2013; Leroy, Ruel, and Verhofstadt 2009). Although there is a consensus regarding the need to invest in nutrition-sensitive programs in order to address the underlying causes of undernutrition and to improve the effectiveness, reach, and scale of both nutrition-specific interventions and nutrition-sensitive programs, the evidence of what works, how, and at what cost is extremely limited. Thus, building a strong body of evidence from rigorous, theory-based comprehensive evaluations of different nutritionsensitive program models that bring together interventions from a variety of sectors (health, education, agriculture, social protection, women’s empowerment, water and sanitation, and so on) is essential to provide the needed guidance for future investments for improving nutrition. This chapter provides this type of guidance, focusing on how to design and carry out rigorous process, cost, and impact evaluations of complex nutrition-sensitive programs. It aims to demystify some of the perceived insurmountable challenges that have prevented investments in rigorous evaluations of such programs in the past. By doing so, we hope that the evidence gap in nutrition-sensitive programming, which has characterized the past decades of development, will quickly be filled and that future investments will benefit from a strong body of evidence on what works to improve nutrition, how it works, and at what cost.